Application of the Use of Digital Media in Learning Solar System in Elementary School - Dennis Surya Putra; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2022)
This research aims to find out how elementary school students respond to teaching about the definitions and concepts of the Solar System using digital media. The researcher uses a quantitative method with a Pre-Experimental Design model to support this research because the data collected and the analysis are quantitative. The target of this research is students in elementary school, which is then taken as a sample of 20 students from sixth grade in Bandung Regency, Indonesia for research. The media used during the research were powerpoint and Infographics. The research was carried out offline and one class was divided into two groups, namely Group A and Group B. The results of this study indicate that the use of digital media in science learning material for the Solar System is declared effective, as can be seen from the results of the pre-test and post-test which show improvement, especially in the aspect of students' knowledge in understanding the material of the Solar System. The Pre-Test shows that almost all respondents do not know much about the solar system. However, when given learning materials using digital media such as powerpoint and Infographics, respondents, namely students, understood and understood the material as evidenced by the Post-Test results. Therefore, it can be concluded that in this study, the application of digital media to elementary school students can be implemented properly.